Between the state and the individual: 'Big Society' communitarianism and English Conservative rhetoric. (April 2015) - Gibson, Howard
During his quest for leadership of the English Conservative Party, David Cameron declared his intention to turn Britain into a Big Society. In May 2010, having gained office as Prime Minister, he unveiled a string of policies to bring his vision to fruition. After five years, however, talk of the Big Society has withered in public debate such that today only the press refer to it, and then as a policy in decline. This article argues that as an attempt to revitalise citizenship and local communities, and deal with the apparent ills of state centralism and liberal atomism, it was destined to fail. This is because it coincided, intentionally some have said, with an austerity crisis that made talk of the Big Society politically feasible; left Big Capitalism, the cause of austerity, untouched; was seemingly reticent to divert power to localities; under-theorised the nature and complexity of modern communities; and was an attempt at depoliticisation by diverting risk to bodies such as charities and schools.